Stochastic frontier analysis on technical efficiency of strawberry farming in purbalingga regency Indonesia - Irene Kartika Eka Wijayanti,; Jamhari Jamhari,; Dwidjono, Hadi Darwanto; Any Suryantini (Universitas Gadjah Mada, 2020)
The objective of this study is to determine technical efficiency and factors affecting technical inefficiency of strawberry farming in Purbalingga Regency. This study was conducted in Karangreja Subdistrict, Purbalingga Regency, Central Java Province. Purposive sampling method was utilized to select 100 farmers as the respondents. All of whom have been running their farm business for at least three years consecutively from 2015 to 2017. Stochastic frontier production function was applied to measure technical efficiency and factors affecting technical inefficiency. The findings show that strawberry farming in Purbalingga Regency, Central Java Province, is technically efficient with efficiency number varies between 26.50-99.40% and the average efficiency number of 77.80%. Furthermore, the results indicate that the farmers’ formal education and the number of household members significantly affect the technical efficiency of strawberry farming.